2019
DOI: 10.1177/0003702819841913
|View full text |Cite
|
Sign up to set email alerts
|

Application of Mn–Cu Helical Star-Shaped (Pine-Tree-Like) Sculpted Thin Films with Different Symmetries Using Surface-Enhanced Raman Spectroscopy (SERS)

Abstract: In this work, the surface engineering method is used to produce Mn helical star-shaped (pine-tree-like) nanosculptured thin films with three-, four-, and fivefold symmetries on Cu substrates using an oblique angle deposition technique together with rotation of the sample holder at certain angles. Nano structure and morphologies of the produced samples were obtained by means of atomic force microscope and field emission scanning electron microscope. Raman spectroscopy of the Mn/Cu samples impregnated by 4,4′-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Combined with the observation of AFM, Raman, and XPS, the composition and Surface-enhanced Raman spectroscopy (SERS) has been widely investigated by cladding Ag and Au films onto the surface of all kinds of samples, but little work is concerned with the transition metal coating. Recently, some organic films have demonstrated the SERS behaviors, including the Mn nanostructures [31]. This suggests that the abnormal Raman peak intensity observed in MnGe/Si QDs can be attributed to the surface-enhanced Raman scattering from Mn sites.…”
Section: Resultsmentioning
confidence: 99%
“…Combined with the observation of AFM, Raman, and XPS, the composition and Surface-enhanced Raman spectroscopy (SERS) has been widely investigated by cladding Ag and Au films onto the surface of all kinds of samples, but little work is concerned with the transition metal coating. Recently, some organic films have demonstrated the SERS behaviors, including the Mn nanostructures [31]. This suggests that the abnormal Raman peak intensity observed in MnGe/Si QDs can be attributed to the surface-enhanced Raman scattering from Mn sites.…”
Section: Resultsmentioning
confidence: 99%
“…Sculptured structures can be designed and fabricated under controlled deposition conditions with sharp tips and recesses with chosen numbers and sizes. Our work [23] showed that the geometry (shape and size) and symmetry of the metal substrate is as important and effective as choosing the metal itself and also cheaper metals such as Mn can produce better results than Au and Ag metals. Hence, they can have high applications in industry and medicine.…”
Section: Introductionmentioning
confidence: 88%
“…The structures of the samples produced for this work are given in our earlier work [23]. However, in order to give the facility of ease of access to these data to the reader, they are repeated here with a brief description.…”
Section: Sem and Afm; Nano-structurementioning
confidence: 99%
See 1 more Smart Citation
“…Sculptured thin films consist of columnar structures which their growth is being controlled by movement of the substrate. Complex structures such as nano-star [24,25], chiral nano-zigzag [26], nano-square [27], chiral nano-flower [28] shaped sculptured thin films are produced, and their optical properties are investigated both experimentally [28], and theoretically [29][30][31]. 3D sculptured nanostructures fabricated by these methods have a vast area of applications such as optical filters [32], reflectors [33], polarizers [34], sensors [35,36], bio-scaffolds [37], and micro-channels [38].…”
Section: Introductionmentioning
confidence: 99%